2018
DOI: 10.1049/iet-nbt.2017.0139
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of titanium dioxide nanoparticles with volatile oil ofEugenia caryophyllatafor enhanced antimicrobial activities

Abstract: Different chemo-physical methods are used to synthesise titanium oxide nanoparticles (TiO NPs), which are often expensive, unfriendly to the environment, toxic, not biocompatible, with a small yield. To resolve these problems, the researchers use green procedures to synthesise TiO-NPs by plant extracts of L. and (onion) and characterise using atomic force microscopy, scanning electron microscopy, transmission electronic microscopy, X-ray diffraction, ultraviolet (UV)-visible (Vis) spectra and Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, studies using plant extracts as bioreductants to synthesize TiO 2 NPs are limited. To date, studies reported the synthesis of TiO 2 NPs from a range of (medicinal) plants (mostly aqueous leaf extracts) including Acacia nilotica (gum Arabic tree) [26], Citrus limon (lemon) [39], A. vera [40], Allium cepa (onion) [41], Trigonella foenum-graecum (fenugreek) [42], Curcuma longa (turmeric) [43], Azadirachta indica (neem) [44][45][46], Euphorbia prostrata (spurge spp.) [47], Psidium guajava (guava) [48], Eclipta prostrata (false daisy) [49], Nyctanthes arbor-tristis (night jasmine) [50], Catharanthus roseus (bright eyes) [51], but most of their applications have been focused on infectiology (as antimicrobials).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies using plant extracts as bioreductants to synthesize TiO 2 NPs are limited. To date, studies reported the synthesis of TiO 2 NPs from a range of (medicinal) plants (mostly aqueous leaf extracts) including Acacia nilotica (gum Arabic tree) [26], Citrus limon (lemon) [39], A. vera [40], Allium cepa (onion) [41], Trigonella foenum-graecum (fenugreek) [42], Curcuma longa (turmeric) [43], Azadirachta indica (neem) [44][45][46], Euphorbia prostrata (spurge spp.) [47], Psidium guajava (guava) [48], Eclipta prostrata (false daisy) [49], Nyctanthes arbor-tristis (night jasmine) [50], Catharanthus roseus (bright eyes) [51], but most of their applications have been focused on infectiology (as antimicrobials).…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 nanoparticles were chosen because they act as a photocatalyst to kill microorganisms. In addition, TiO2 has a low cost, stability, low toxicity, high ultraviolet absorbance, and a high energy gap (i.e., 3.2–5.2 eV) 3 , 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Titanium, copper, and silver nanoparticles are examples of metallic nanoparticles. Titanium dioxide (TiO2) has unique properties, such as a low cost, stability, low toxicity, high refractive index, high optical properties, high ultraviolet absorbance, strong redox ability, high energy gap (i.e., 3.2–5.2 eV), and has good electrical, optical and magnetic properties 3 , 4 . It is necessary to fully define the characteristics of nanoparticles, such as their size, shape, surface morphology, crystallinity, and light absorption, using appropriate characterization techniques 5 , such as microscopy techniques (electron microscopy or scanning probe microscopy).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, titanium oxide has been commercially used especially as a white pigment in paints, colorants, plastics, coatings, cosmetics, and so on [1]. Recently, furthermore, it has been also reported that some kind of titanium oxide showed antimicrobial activity [2]. Thus, Ti‐based materials possess attractive possibilities to advance a wide range of clinical and industrial applications.…”
Section: Introductionmentioning
confidence: 99%